A regulated fishing policy to support food security in the marine and fisheries sector - Rifai, Rizal (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: Indonesia, as the world's largest archipelagic country, holds vast marine resources crucial for national food security. However, the increasing fish consumption coupled with unsustainable fishing practices has led to overfishing, impacting marine ecosystems and food security. To address this, a measured fishing policy is essential to optimize fish harvest while ensuring marine sustainability. Methods: This study employs a qualitative descriptive analysis method through a literature review approach. It examines concepts related to food security, the Blue Economy, and the implementation of measured fishing policies. Data are collected from scientific references, national policies, and international regulations to identify control instruments and develop comprehensive policy recommendations. Findings: The findings indicate that measured fishing, characterized by regulated fishing quotas, vessel numbers, and fishing zones, is effective in preventing overfishing while ensuring food security. The strategy includes setting quotas aligned with ecosystem capacity, managing vessel numbers, establishing integrated monitoring systems, and optimizing non-tax state revenue (PNBP). Additionally, empowering small-scale fishers and ensuring inter-sectoral synergy are crucial for sustainable fisheries management. Conclusion: Measured fishing policies significantly contribute to national food security by balancing economic growth and marine ecosystem sustainability. The implementation of this policy enhances fish resource management and supports the welfare of coastal communities. Novelty: This study offers a comprehensive framework for measured fishing policy as a strategic solution to overfishing, integrating sustainable practices with economic empowerment. It also highlights the role of Blue Economy principles in supporting Indonesia's food security and sustainable marine resource management.